Educational system contrasts between Ecuador and Colombia (2023)
The article aims to carry out a comparative study of the educational development between Colombia and Ecuador. It aims to understand the actions that have been implemented in education and to identify the legal aspects that support the educational system. This comparative education study is based on a bibliographic analysis of laws, curricula and guidelines, which allows us to study two countries with similar profiles in the educational, social and economic fields but different actions in the field of educational practice. Among the findings of this study, the following are common aspects: in addition to the need for a unified curriculum, the existence of norms governing school entrepreneurship, and the compulsory nature of the levels of education. On the other hand, mismatches were found in the practical measures adopted to incorporate entrepreneurship education in educational institutions offering different levels of education. The progress of education among South American countries was recognized, with their main needs and prospects for investment in education, evaluation of the quality of education, policies related to ICTs and the need to emphasize the importance of teachers in society.